(untitled) (Italiano LinguaDue, 2021)
Il presente contributo discute i risultati di un’indagine esplorativa sulle pratiche di didattica delle lingue a distanza messe in atto da un campione di oltre 1.000 insegnanti di lingue straniere all’inizio dell’emergenza sanitaria da COVID-19 in Italia. I dati sono stati raccolti attraverso un questionario e analizzati sul piano sia quantitativo sia qualitativo. Pur non consentendo generalizzazioni, i risultati dell’indagine offrono indicazioni sui fattori-chiave da considerare per progettare e implementare interventi efficaci di didattica delle lingue a distanza. Teaching foreign languages at a distance in an emergency situation: the results of a sample survey The paper reports the results of a survey that explored the distance language teaching practices employed by a sample of more than 1.000 foreign language teachers at the beginning of the COVID-19 emergency in Italy. Data collection took place by means of a questionnaire and the answers were analyzed both quantitatively and qualitatively. Although the research findings cannot be generalized, they provide insights on the key-factors that need to be taken into account in order to effectively design and implement distance language teaching.